Application of space-time disease clustering by administrative databases in Italy: Adverse Reproductive Outcomes (AROs) and residential exposure. Issue 1 (December 2015) - Barbadoro, Pamela; Agostini, Massimo; D'Errico, Marcello; Di Stanislao, Francesco; Filippetti, Fabio; Giuliani, Sara; Prospero, Emilia
Abstract Background The aims of this study were to estimate the existence of clusters of AROs in the municipalities of the Marches Region (Central Italy) after complaints from residents living near an abandoned landfill site. Methods Cases of AROs (i.e., congenital malformation, chromosomal abnormalities, and low birth weight) were retrieved from hospital discharge data. SaTScan and GeoDa were used to check for the presence of clusters at a regional and a small area level. Moreover, at a small area/neighborhood level, smoothed rates were calculated, and a case–control approach was used to assess the residence in proximity to the abandoned landfill as an independent risk factor for AROs. Results AROs were associated with the price per square meter of the accommodations in the area of residence (OR 2.53, 95 % CI 2.06-3.10). On the other hand, residence within one kilometer of the landfill (OR 0.04, 95 % CI 0.01-0.23) and maternal age greater than 35 years (OR 0.96, 95 % CI 0.92-0.99) were protective. Conclusions Residency in proximity to the abandoned landfill was not a risk factor for the occurrence of AROs. The results show that basic information, such as the price of accommodations in different neighborhoods, could be of interest in order to target training programs for women living in difficult conditions and highlights the potential role of the building environment in perinatal health. However, we note that aside from the data provided by Geographic Information Systems in public health, collection of the patient's residential address was unreliable for selected conditions. Future efforts should emphasize the patient's residential address as information important for evaluating the health of individuals instead of being merely administrative data.